Hydrogenation of polyaromatic compounds over NiCo/chrysotile catalyst - Baikenov, M.I.; Aitbekova, D.E.; Balpanova, N.Zh.; Tusipkhan, A.; Baikenova, G.G.; Aubakirov, Y.A.; Brodskiy, A.R.; Fengyun, М.; Makenov, D.K. (KU Publ., 2021)
The activity and selectivity of the bimetallic NiCo/chrysotile catalyst during the hydrogenation of model objects (anthracene and phenanthrene) for 1 hour at an initial hydrogen pressure of 3 MPa and a temperature of 400 °C were studied. The chrysotile mineral used as a substrate for active centers of nickel and cobalt is a waste product of asbestos production at Kostanay Minerals JSC (the Republic of Kazakhstan). The catalyst was characterized by a complex of methods of physical and chemical analysis. The chrysotile mineral consists of nanotubes with an inner diameter of about 10 nm and an outer diameter of about 60 nm. The amount of hydrogenation products is 61.91 %, destruction — 15.08 % and isomerization — 8.37 % during the hydrogenation of anthracene. The amount of hydrogenation products is 26.09 %, and that of destruction is 2.51 % during the hydrogenation of phenanthrene. It was found that the catalyst selectively accelerates the hydrogenation reaction and allows increasing the yields of hydrogenation products. The schemes of the hydrogenation reaction of model objects were drawn up according to the results of gas chromatography-mass spectrometric analysis of hydrogenates.
Полиароматты қосылыстардың NiCo/хризотил катализаторында гидрогенизациялау
Гидрогенизация полиароматических соединений на катализаторе NiCo/хризотил
Keywords: polyaromatic hydrocarbons; anthracene; phenanthrene; nanocatalyst; hydrogenation; hydrogenation; nickel; cobalt